Pattern of Hematological Manifestations in Patients with Systemic Lupus Erythematosus Attending in a Tertiary Care Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Hematological abnormalities are frequently encountered in patients with SLE. It was aimed to study the pattern and frequency of hematological abnormalities in patients with SLE. Forty patients were prospectively analyzed who were suffering from SLE in the CMCH over a period of one year. All patients were evaluated according to the case record form with particular reference to hematological manifestations. Most patients were females in the child bearing age. Hematological manifestations were documented in87.5% of patients. Anemia was the most common hematological abnormality detected (57.5%). Iron deficiency anemia(IDA) 60%, Anemia of chronic disease(ACD) 26.9% and Autoimmune hemolytic anemia(AIHA) 8.7 % were the most common cause of anemia detected. The data demonstrated that while hematological manifestations are very common in SLE but they are rarely life threatening.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19420